Modern aspects in anesthesia of small laboratory animals - S. V. Gurova; M. V. Mindar; D. V. Khodakova (Южно-Российский онкологический журнал, 2022)
Experiments with small laboratory animals are required for better understanding of a disease flow, for studying the mechanisms of it’s development and for the development of new therapeutic strategies. A significant part of experimental studies involve anesthesia. In this regard, the choice of the optimal anesthesia protocol is an important point of research, since an inadequate depth of anesthesia or the influence of undesirable factors can lead to death; the type, duration, and goals of the procedure should be also taken into account.We have aimed to find out what has changed in anesthesia of laboratory animals lately, which drugs are currently relevant and what is the reason for their popularity.Anesthesia of mice is challenging for several reasons: animal size, metabolic rate, and high risk of hypothermia and hypoglycemia. In addition, anesthetics affect physiological parameters and therefore even more affect the results of experiments. At the moment, there is a large list of drugs used in laboratory animals. Since they are divided into groups depending on the routes of administration, we selected the following drugs from a number of articles: injectable anesthetics (medetomidine, dexmedetomidine, zoletil‑100, ketamine, xyla, propofol) and inhalation anesthetics (isoflurane, sevoflurane). Advantages and disadvantages of the drugs and their combinations were studied and described.An analysis of the literature showed that injection anesthesia is considered the main method of anesthesia for experimental animals and is relatively well tolerated by animals; it also does not require additional bulky equipment and additional staff qualifications, there are antagonists for a number of drugs, and is also affordable.In the majority of studies inhalation anesthesia was used in long-term complex manipulations/operations, since it is more manageable, agents require minimal metabolism, and in some cases do not require additional sedation.